Staphylococcus aureus Colonization: Modulation of Host Immune Response and Impact on Human Vaccine Design - Brown, Aisling F.; Leech, John M.; Rogers, Thomas R.; McLoughlin, Rachel M. (Frontiers in Immunology, 2014)
In apparent contrast to its invasive potential Staphylococcus aureus colonises the anterior nares of 20-80% of the human population. The relationship between host and microbe appears particularly individualised and colonisation status seems somehow predetermined. After decolonisation, persistent carriers often become re-colonised with their prior S. aureus strain, whereas non-carriers resist experimental colonisation. Efforts to identify factors facilitating colonisation have thus far largely focussed on the microorganism rather than on the human host. The host responds to S. aureus nasal colonisation via local expression of antimicrobial peptides, lipids and cytokines. Interplay with the co-existing microbiota also influences colonisation and immune regulation. Transient or persistent S. aureus colonisation induces specific systemic immune responses. Humoral responses are the most studied of these and little is known of cellular responses induced by colonisation. Intriguingly, colonised patients who develop bacteraemia may have a lower S. aureus-attributable mortality than their non-colonised counterparts. This could imply a staphylococcal-specific immune ‘priming’ or immunomodulation occurring as a consequence of colonisation and impacting on the outcome of infection. This has yet to be fully explored. An effective vaccine remains elusive. Anti-S. aureus vaccine strategies may need to drive both humoral and cellular immune responses to confer efficient protection. Understanding the influence of colonisation on adaptive response is essential to intelligent vaccine design, and may determine the efficacy of vaccine-mediated immunity. Clinical trials should consider colonisation status and the resulting impact of this on individual patient responses. We urgently need an increased appreciation of colonisation and its modulation of host immunity.